Why budgets matter : budget policy and American politics - Ippolito, Dennis S. (The Pennsylvania State University Press, 2015)
"Provides a comprehensive account of how conflicts over taxes, spending, deficits, and debt have shaped American political development from the nation's founding until today"--Provided by publisher.